MMX‐I: data‐processing software for multimodal X‐ray imaging and tomography. (14th April 2016) - Bergamaschi, Antoine; Medjoubi, Kadda; Messaoudi, Cédric; Marco, Sergio; Somogyi, Andrea
Abstract : The MMX‐I open‐source software has been developed for processing and reconstruction of large multimodal X‐ray imaging and tomography datasets. The recent version of MMX‐I is optimized for scanning X‐ray fluorescence, phase‐, absorption‐ and dark‐field contrast techniques. This, together with its implementation in Java, makes MMX‐I a versatile and friendly user tool for X‐ray imaging. Abstract : A new multi‐platform freeware has been developed for the processing and reconstruction of scanning multi‐technique X‐ray imaging and tomography datasets. The software platform aims to treat different scanning imaging techniques: X‐ray fluorescence, phase, absorption and dark field and any of their combinations, thus providing an easy‐to‐use data processing tool for the X‐ray imaging user community. A dedicated data input stream copes with the input and management of large datasets (several hundred GB) collected during a typical multi‐technique fast scan at the Nanoscopium beamline and even on a standard PC. To the authors' knowledge, this is the first software tool that aims at treating all of the modalities of scanning multi‐technique imaging and tomography experiments.